THE EFFECT OF INTEGRATED CHEMISTRY PRACTICE LEARNING IMPLEMENTATION ON STUDENT LEARNING OUTCOMES - Wisudawan, Devi (Transpublika Publisher, 2022)
This research aims to determine the effect of integrated chemistry practice implementation on student learning outcomes. This research is a quasi-experimental and unbalanced control experiment design. The population for this research was students in class X for the academic year 2020/2021, totaling 165 students divided into six classes of 24-29 students each. A random sample of 58 pupils from the population was drawn and divided into two classes using a random sampling procedure. The test is included into the data collection procedure utilized in this investigation. Analyze the prerequisites using the normality and homogeneity tests. The descriptive statistical analysis and t-test were utilized to analyze the data for the one-party Separated variant model. The outcomes of the analysis are given a significance level of 5%. The findings reveal that, students who complete comprehensive exercises using integrated practicum approaches achieve higher basic chemistry learning values when compared to students who complete cooperative learning in chemistry (control classes). Integrated practice learning approaches, as demonstrated here, have a significant influence on the educational accomplishment of students at SMK PGRI 3 Malang.